Mayo Adhesive Probability (MAP) score of non-donated kidney aids in predicting post-operative renal function following donor nephrectomy - Katherine J. Cockerill (BMC Urology, 2020)
Abstract Background To examine the association of preoperative Mayo Adhesive Probability (MAP) scores in the donor (MAPd) and non-donor kidneys (MAPnd) with post-donation renal function. Methods Three hundred thirty-one patients undergoing hand assisted laparoscopic donor nephrectomy (HALDN) were reviewed. MAPd and MAPnd were obtained. Estimated glomerular filtration rate (eGFR) was recorded preoperatively and at 1 day, 1 month, and 6 months postoperatively. Results Two hundred females and 131 males were evaluated with median BMI 26.4 kg/m2 (range 17.1–39.6) and median age 45 years (range 19–78). MAPd score was 0 for 231 patients (69.8%) and > 0 for 100 patients (30.2%). MAPnd score was 0 for 234 patients (70.7%) and > 0 for 97 patients (29.3%). The median preoperative eGFR was 86.6 ml/min/1.73m2 (range 48.8–138.4). After adjusting for preoperative eGFR, BMI, ASA score, and kidney sidedness, postoperative eGFR was associated with MAP score in the non-donated kidney (p = 0.014) but not in the donated kidney (p = 0.24). Compared to donors with MAPnd = 0, donors with a MAPnd > 0, mean eGFR was − 2.33 ml/min/1.73m2 lower at postoperative day 1 (95% CI − 4.24 to − 0.41, p = 0.018), − 3.02 ml/min/1.73m2 lower at 1 month (95% CI − 5.11 to − 0.93, p = 0.005), and − 2.63 ml/min/1.73m2 lower at 6 months postoperatively (95% CI − 5.01 to − 0.26, p = 0.030). Conclusions MAP score > 0 in the non-donated kidney is associated with worse renal function in the 6 months following HALDN.